Development of speed qualities of skilled water-polo players - Ostrovsky M.V (Kharkov National Pedagogical University, 2010)
Swimming preparation of water-polo players is the basic factor of victory of command. There are a few variants of development of speed swimming preparation. The effective pedagogical mean of stimulation of speed qualities is brief exercises at the end of employments after long aerobic work. The purpose of work is an improvement of method of speed preparation of skilled water-polo players. 26 skilled water-polo players (MS -14 and KMS - 12) took part in an experiment in age from 21 to 32 years. The results of correction of structure of training employment are in-process presented in micro cycle. They are directed on the improvement of speed qualities of water-polo players.